ACETIC ACID FORMATION STUDY IN COCOA SWEATINGS TREATMENT UNDER ANAEROBIC CONDITION - Mahensa Billqys Nurhayati Prativi (Pusbindiklat - LIPI, 2013)
This research aimed to study the possibility of cacao sweatings treatment to produce intermediate compound i.e. acetic acid in acidogenesis processes. It were carried on an anaerobic Circulating Bed Reactor which is made from flexyglass 6 L capacities and operated in batch system. The operation of two circulating bed reactor conducted at room temperature for 20 days and nitrogen gas flushing is performed at one of the reactor for 10 minutes in the beginning of operation. Gas composition analysis indicates the persistence of O2 in reactor A, hence the acetic acid formation follows the aerobic pathway and occurs more rapidly. Concentration of O2 in reactor B is relatively low compared to reactor A. So that is concluded that acetic acid formation reach the anaerobic pathway and run slowly. This research indicates that the presence of O2 in the reactor affect the pathway of acetic acid formation.